Estimation of important binding sites in compounds that interact with proteins. (August 2021) - Tachibana, Kouhei; Fukazawa, Aoi; Nishide, Ryo; Ohkawa, Takenao
Abstract: Proteins are one of the important substances in understanding biological activity, and many of them express the function by binding to other proteins or small molecules (ligands) on the molecular surface. This interaction often occurs in the hollows (pockets) on the molecular surface of the protein. It is known that when pockets are similar in structure and physical properties, they are likely to express similar functions and to bind similar ligands. Therefore, exploring the similarity of the structure and physical properties in pockets is very useful because it leads to the discovery of new ligands that are likely to bind. In addition, exploring the important structure when binding to the protein significant spot in the ligand will provide useful knowledge for the development of new ligands. In this study, we propose a method to search for proteins containing pockets that are structurally and physically similar to significant spot in the pocket of the analyzed protein, and to extract significant spots in the ligands that bind to them. We use feature points as data. Feature points are the 3-dimensional points that are extracted from 3D structure data of proteins with feature values quantifying hydrophobicity and electrostatic potential. The corresponding feature points are extracted by comparing structurally and physically the pockets of the search target proteins with the significant spot of the analyzed protein. By evaluating the similarity based on the comparison results of the feature values given to the extracted feature points, we search for proteins that are similar to the analyzed protein. From the ligands that bind to the searched proteins, atoms that are near the protein pocket and similar to the atoms in ligand binding to the analyzed protein are extracted. The site constituted by the extracted atoms is defined as a significant spot in the ligand. As a result of classifying ligands binding to the protein by using the extracted significant spot in the ligand, the effectiveness of the proposed method was confirmed.